Redefining Electronic Health Records (EHR) and Electronic Medical Records (EMR) to Promote Patient Empowerment - Muhammad Anshari (IJID (International Journal on Informatics for Development), 2019)
A successful healthcare organization exists when it provides good quality service. Powered by technological changes like big data, cloud computing, and Internet of Things, healthcare information is accessed and owned and the patient has become evolving within the healthcare environment. This affects the relationship between healthcare provider and customers, and between patients. Electronic Health Records (EHRs) and Electronic Medical Records (EMRs) are considered as a building block for electronic health development. Many literatures use both terms EHR and EMR interchangeably with no clear distinction in terms of scope and dimensions. The aim of the research is to examine the distinct role of EHR from EMR in order to promote patients’ empowerment.  While, patient empowerment in e-health will enhance patients’ satisfaction, improve their health literacy, and involve patient in the process of health decision making.